2019
DOI: 10.1186/s13287-019-1511-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes the BMP9-induced osteogenic differentiation of mesenchymal stem cells by activating the AMPK/β-catenin signalling pathway

Abstract: BackgroundMesenchymal stem cells (MSCs) play a crucial role in maintaining the dynamic balance of bone metabolism. Melatonin may have a regulatory effect on bone metabolism by regulating the lineage commitment and differentiation signalling pathways of MSCs. Among the BMP families, the osteogenesis of BMP9 is considered to be one of the strongest in MSCs. Here, we explored whether melatonin and BMP9 act synergistically on MSC osteogenic differentiation.MethodsThe C3H10T1/2 osteogenic differentiation function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…In this regard, MSCs pulsed with tumor-derived microvesicles showed an enhanced antitumor activity in HCC [ 166 ]. Some previous report revealed the use of melatonin enhanced the potential therapeutic role MSCs in treatment various diseases such as acute kidney injury, metabolic syndromes including diabetes through various mechanisms that include through the activation of antioxidative pathways, inhibition of the inflammatory response and reduction of apoptosis and fibrosis [ 19 , 167 , 168 , 169 , 170 ]. More interestingly, few recent reports revealed the beneficial effects of the combination between melatonin and MSCs on targeting inflammation in HCC [ 171 , 172 , 173 , 174 , 175 ].…”
Section: Potential Beneficial Effect Of the Combination Between Mementioning
confidence: 99%
“…In this regard, MSCs pulsed with tumor-derived microvesicles showed an enhanced antitumor activity in HCC [ 166 ]. Some previous report revealed the use of melatonin enhanced the potential therapeutic role MSCs in treatment various diseases such as acute kidney injury, metabolic syndromes including diabetes through various mechanisms that include through the activation of antioxidative pathways, inhibition of the inflammatory response and reduction of apoptosis and fibrosis [ 19 , 167 , 168 , 169 , 170 ]. More interestingly, few recent reports revealed the beneficial effects of the combination between melatonin and MSCs on targeting inflammation in HCC [ 171 , 172 , 173 , 174 , 175 ].…”
Section: Potential Beneficial Effect Of the Combination Between Mementioning
confidence: 99%
“…In addition, it is reported that polydatin improved the osteogenic differentiation of hBMSCs and maintained the bone matrix in the OVX mouse model through the activation of β-catenin pathway [39] . Melatonin promotes the BMP9-induced osteogenic differentiation of mesenchymal stem cells by activating the β-catenin signalling pathway [40] . But inactivation of β-catenin signaling in osteoblasts causedthe increased osteoclastogenesis due to insu cient production of OPG [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Alizarin Red and Alkaline phosphatase ( ALP) staining were performed according to a previously described procedure ( 17 ).…”
Section: Methodsmentioning
confidence: 99%